Design of distillation column control systems - Buckley, Page S. (Edward Arnold ; Instrument Society of America, 1985)
This book was written primarily from the standpoint of an engineering design organization, and based on years of experience with large design projects as well as on personal plant experience. Most new investment dollars go into new or modernized facilities, and it is in the design phase of projects for these facilities that the most opportunities occur and flexibility exists to influence process control. Consequently this book is aimed primarily at design personnel; however, it will also be useful to those who have to operate or troubleshoot existing plants. It is the purpose of this book to indicate the range of technology, which has been developed for distillation control, to the point where it can be economically and reliably used for design.